Prevalence and risk factors of low birth weight: a systematic review - Nyi Nyi, Naing; Wan Arfah Nadiah, Wan Abdul Jamil; Tahira, Ashraf (2020)
Background: Low Birth Weight (LBW) is a critical health issue with serious feto-maternal outcomes. Maternal risk factors are associated with LBW therefore it is important to review published studies systematically for the prevalence of LBW and determine its significant risk factors. Objective: To review published prevalence and risk factors of low birth weight from years 2009-19 Materials and Methods: All full-length studies done on the prevalence and/or risk factors of LBW freely available on the internet using Search engines like Google scholar, the web of science, Cochran library and PubMed, with the BOOLEAN search strategy. 13 articles were shortlisted after critical analysis using PRISMA guidelines. Endnote version 7 was used to store these studies which were later critically reviewed. Results: The studies published from 2009-19 were selected. The prevalence of LBW ranged from 6.16-38%. Maternal sociodemographic (young maternal age, lack of education, low socioeconomic status and residence in a rural area), medical (Maternal anemia, preeclampsia, history of other maternal diseases and complications such as renal diseases, UTI, HIV, venereal disease, bleeding during pregnancy, history of abortion or LBW baby) and antenatal factors (lack of antenatal care, unbooked delivery status, and not taking IAF regularly) were significantly associated with LBW. Conclusion: Low Birth Weight remains to be a challenge as its prevalence is high worldwide. Maternal socio-demographic, maternal and antenatal risk factors are significantly associated with low birth weight. This review may help policymakers to design specific interventions targeting the prevention of low birth weight in the future.